Potensi Endofit Akar Bambu sebagai Biokontrol Patogen Fusarium oxysporum Penyakit Kuning Tanaman Lada - Ropalia Ropalia (Universitas Bangka Belitung, 2017)
The yellowing disease on pepper plant (Pipper nigrum L) caused by plant-parasitic nematodes and F. oxysporum infection is a major disease in Bangka island. The wound that caused by plant-parasitic nematodes will facilitate infection into roots by the pathogen of F. oxysporum easily. This caused the plant sensitive to drought and nutrient deficiency. Utilization of endophytic microbes is one of biological control that environmental friendly and to support sustainable agriculture. The aim of this study was to explore endophytic isolates can inhibit the growth of F. oxysporum in vitro. The endophytes were isolated from bamboo root and selected their antagonistic potential against F.oxysforum by dual culture methods. The study resulted an endophytic bacteria and 13 isolates of endophytic fungi that inhibit mycelium growth of F. oxysforum. The antagonistic activity of endophytic bacteria to F. oxysforum is 28.25% by antibiosis mechanism and endophytic fungi, about 11.00-58.25% by space colonization and nutrition competition on substrate.